Arc-welders' pneumoconiosis with atypical radiological and bronchoalveolar lavage fluid findings: A case report. (2020) - Yamamoto, Yuji; Tsujino, Kazuyuki; Urasaki, Koji; Matsuki, Takanori; Fukushima, Kiyoharu; Kida, Hiroshi
Abstract: Arc-welders' pneumoconiosis (AWP) is an occupational lung disease and has nonspecific symptoms typically with the patterns of centrilobular and/or branching opacities on chest high-resolution computed tomography (HRCT) which are similar to those of hypersensitivity pneumonitis (HP) and/or respiratory tract infections. Therefore, the differential diagnosis is often difficult if they are not suspected. We report a case of AWP which was initially suspected to be pulmonary tuberculosis because of the chest HRCT findings: centrilobular opacities distributed predominantly on the right lobe. On detailed review of the work history, however, the patient was found to be involved in welding. Prussian blue staining of the lung tissues and the bronchoalveolar lavage fluid (BALF) ferritin analysis were useful for the final diagnosis and the appropriate treatment for AWP. The atypical lymphocytosis in BALF in this case suggested the involvement of HP in the pathogenesis due to the occupational sensitization to causal antigens. To the best of our knowledge, this is the first case report of AWP showing features of HP. AWP should be noted even in patients with the typical patterns of centrilobular opacities on chest HRCT. Medical history, iron staining of lung tissues, and the BALF ferritin analysis would be useful for the diagnosis of these patients. The BALF findings are sometimes indeterminate for the diagnosis because the occupational sensitization to causal antigens might be involved in some cases of AWP.